Ibuprofen release from porous hydroxyapatite tablets - Oner, Mualla; Yetiz, Erman; Ay, Esin; Uysal, Umut (ELSEVIER SCI LTD, 2011)
The present study investigated drug release profiles from porous hydroxyapatite [Ca-5(PO4)(3)OH, HAP] tablets. HAP tablets prepared synthetically and porous structure was generated via microemulsion after sintering at 700 degrees C. The influence of tablet's microemulsion concentration on drug release profiles from sintered porous tablets was investigated by using ibuprofen (C13H18O2) as model drug. A numerical approach based on Fick's second diffusion law was used to investigate drug release kinetics from porous HAP tablets. Via this equation, diffusion coefficients were calculated for each tablet and compared. Drug release from the tablets was influenced by the porosity and tortuosity of the porous network. The drug release from porous HAP tablets was increased by microemulsion concentration. It is possible to obtain HAP based drug delivery system which has different drug release behavior by controlling microemulsion concentration in tablets before sintering. (C) 2011 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Biomedical applications; Hydroxyapatite; Drug release; Ibuprofen; CALCIUM-PHOSPHATE CEMENT; DRUG-DELIVERY SYSTEM; MIXING SOLUTION VOLUME; IN-VITRO; INDOMETHACIN RELEASE; TEMPERATURE; FABRICATION; MCM-41; Materials Science